2013
DOI: 10.2217/bmt.13.52
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk scores in a standard screening population

Abstract: Demographics -The ethnicity of the sample population was highly heterogeneous, but comparable to the population at large. -Almost a third of participants had a relative with breast cancer. -26 out of 355 women were recalled for further investigation.Risk scores -In our sample, the mean 5-year risk score according to the modified Gail model was 1.5%; the lifetime risk score was 9%. Risk factors & the potential for modification-A substantial proportion of the women reported modifiable risk factors (23% with curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 70 publications
0
9
2
Order By: Relevance
“…In terms of lifetime risk, the result of 5.3% in present study is consistently lower than all other studies in the U.S. (12.3%) [31], Iran (9.0%) [27], Korea (7.9%) [28], Turkey (15%) [29] and the United Kingdom (9.0%) [30]. In addition, the proportion of Chinese women who had a five-year risk > 1.66% were also lower than the other studies [28,30]. Overall, the Chinese women in this study population were found to have generally lower risk of breast cancer based on the risk assessment of the Gail Model.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In terms of lifetime risk, the result of 5.3% in present study is consistently lower than all other studies in the U.S. (12.3%) [31], Iran (9.0%) [27], Korea (7.9%) [28], Turkey (15%) [29] and the United Kingdom (9.0%) [30]. In addition, the proportion of Chinese women who had a five-year risk > 1.66% were also lower than the other studies [28,30]. Overall, the Chinese women in this study population were found to have generally lower risk of breast cancer based on the risk assessment of the Gail Model.…”
Section: Discussioncontrasting
confidence: 61%
“…Compared to studies outside of the United States, the results of the present study are comparable to the study in Iran [27] and lower than studies in Korea [28], Turkey [29] and the United Kingdom [30]. In terms of lifetime risk, the result of 5.3% in present study is consistently lower than all other studies in the U.S. (12.3%) [31], Iran (9.0%) [27], Korea (7.9%) [28], Turkey (15%) [29] and the United Kingdom (9.0%) [30]. In addition, the proportion of Chinese women who had a five-year risk > 1.66% were also lower than the other studies [28,30].…”
Section: Discussioncontrasting
confidence: 53%
“…The Gail model risk for each subject was calculated by Breast Cancer Risk Assessment Tool (BCRAT) (an interactive tool designed for estimating the women’s risk of developing invasive breast cancer). 12 , 16 - 18 …”
Section: Methodsmentioning
confidence: 99%
“…14 The GM is the most commonly used risk prediction model and has been well studied, validated and applied in various studies worldwide. [15][16][17] Therefore the aim of the current study was to apply the GM2 to the Iraqi population and assess whether it can be used to assess the prediction of BC for the Iraqi women.…”
Section: Introductionmentioning
confidence: 99%